Landfill Reduction In The Context Of Sustainable Waste Management: A Case Study Of Bengaluru (International Journal of Environmental Sciences, 2025)
Municipal solid waste generation is the fundamental problem for Bruhat Bengaluru Mahanagara Palike (BBMP) in Bengaluru due to urbanization and an expansion of population. The main objective of the study is to examine the key stakeholders' waste management practices across Bengaluru city. This study is completely based on the qualitative research method. The key stakeholders of this study are Resident Welfare Associations (RWAs), non-governmental organizations (NGOs), corporate offices, Information Technology (IT) parks, educational institutions, BBMP, temples, and markets. The stakeholders are involved in waste segregation, composting, recycling, and waste-to-energy initiatives. Hence, 39.39% of the city waste is diverted from landfills, and 21.82% of the waste is diverted with the help of windrow composting plants. Additionally, the study recommended that public awareness, participation in waste management activities, enforcement of the various government policies, waste-to-energy projects, and technological interventions in waste management activities are essential to reduce the landfill burden in the city.